Perception of the image in indigenous poetics (2014)
Speech by Betsimar Sepúlveda in Universidad Javeriana (Bogotá, 2012) about the poetic image in Anastasia Candre’s texts, and about indigenous writers who raise their own voices of memory and land. It includes a poem by Betsimar dedicated to Anastasia, and two poems by Juan Rivas and Vicente Arreaza, Pemon poets from Venezuela.